Re-liquefaction of Sand in Shaking Table. Issue 1 (February 2020) - Nepal, Dikshit Babu; Deng, Jianliang; Chen, Jinjian; Maakoe, Tshegofatso
Abstract: Subsequent aftershocks can induce reliquefaction of sand. In the shaking table experiment, the settlement, the excess pore water pressure and the acceleration response of the sand in the process of reliquefaction were measured. It was found that: (1) the liquefaction resistance of sand was the lowest in the second liquefaction, not in the first liquefaction; (2) Liquefaction resistance is depth-dependent, and the soil layer near the surface of soil is most likely to be liquefied; (3) In the model test, the attenuation of seismic shear wave acceleration is not only related to distance but also to the vibration frequency and to the liquefied layer; (4) The amplitude of the acceleration response increases with the number of the shaking. This result indicates that: (1) the phenomenon of re-liquefaction of sand induced by earthquake is not same as that of the first liquefaction. Therefore, the conventional strategy for liquefaction resistance needs to be improved before it can be implemented for analysis of reliquefaction. (2) The attenuation of seismic shear waves in liquefied soil layer has some properties different from the normal soil layer; thus the traditional attenuation calculation method needs improvement in the evaluation in the analysis of site liquefaction.